Social contact and attitudes toward outsiders: The case of Japan - Yusaku Horiuchi; Yoshikuni Ono (Research & Politics, 2023)
Previous studies have shown that people oppose refugee resettlement more strongly after being exposed to frames that depict refugees as threatening. However, all people may not perceive such threats the same way. Based on contact theory, we hypothesize that the treatment effects of threatening frames on people’s opposition to refugee resettlement are conditional on their contact experience with foreign-national residents. The results of our pre-registered experiment in Japan indicate that exposure to threatening information does not change attitudes toward refugee resettlement among those living in municipalities where the number of foreign-national residents is rapidly increasing . Combined with the analyses of other subjective measures of contact with foreigners, some suggestive patterns emerge that natives with conscious and positive interactions with outgroup members may be unaffected by anti-refugee rhetoric and threatening frames.